If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6u + -42 = 6(u + 9) Reorder the terms: -42 + -6u = 6(u + 9) Reorder the terms: -42 + -6u = 6(9 + u) -42 + -6u = (9 * 6 + u * 6) -42 + -6u = (54 + 6u) Solving -42 + -6u = 54 + 6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-6u' to each side of the equation. -42 + -6u + -6u = 54 + 6u + -6u Combine like terms: -6u + -6u = -12u -42 + -12u = 54 + 6u + -6u Combine like terms: 6u + -6u = 0 -42 + -12u = 54 + 0 -42 + -12u = 54 Add '42' to each side of the equation. -42 + 42 + -12u = 54 + 42 Combine like terms: -42 + 42 = 0 0 + -12u = 54 + 42 -12u = 54 + 42 Combine like terms: 54 + 42 = 96 -12u = 96 Divide each side by '-12'. u = -8 Simplifying u = -8
| b=q-v | | -16+12y=-11+11x | | x=20-q | | 11-n=-6n-4 | | 5z-10z=40 | | 30+3q=6q | | a-6=4a+9 | | 258=4x+2 | | 50+.25x=43.50+35x | | 13.6+(3.4c)+1.7c=3.4 | | 7-5r=1-6r | | x-4=-4+4x | | 8+3(2x+7)=5(3x-1) | | 3(y-5)+1=-20 | | (w+6)-5= | | -4k^2+8k-9=0 | | -4x-(9)=13 | | 6x+10=8x+1 | | -300(3(-50))=x | | 3cosx-4sinx=5 | | 3x+(-5)=-20 | | 11-6x=-x+6 | | 5m*3+n=18 | | 50+.25x=43+.50x | | 2x+12-9=-21 | | -300(3(-50))= | | 5m^3+n=18 | | -10-7x=-17 | | -6(3x-8)=48 | | g(5)=x-4 | | 1-6r=10+5r | | 33=5x-9+4x |